PERAN ILMU PENDIDIKAN KRISTEN DALAM MEMBENTUK KEDISIPLINAN SISWA - Melianti Sombolayuk; Grazelia Liza Damayanti; Juwita Arung Langi'na Pasali; Oner Tampang; Darius Rika (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the role of Christian education in shaping student discipline through theological and pedagogical approaches. Disciplinary issues in educational settings, especially Christian schools, have become a serious concern in the modern era characterized by limitless freedom and value relativism. Using a qualitative method through literature study, this research identifies that Christian education provides a strong theological foundation for viewing discipline as an expression of love and a tool for character formation. Teachers play a strategic role as models and mentors of discipline, not merely as instructors but as spiritual shepherds. Disciplinary strategies include spiritual habits, the implementation of love-based rules, and learning communities that instill Gospel values. The findings reveal that Christian educational principles remain relevant and effective in addressing the crisis of student discipline in the digital and postmodern age. Thus, Christian education functions not only as an instructional system but also as a transformative means for shaping holistic and resilient character amidst rapid cultural changes.